Analysis the Effect of Innovation and Creativity to Business Success - Komarudin, Muhammad; Hamdani, Nizar Alam (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to determine the influence of innovation and creativity on business success. In this study, data was collected using a questionnaire method on 40 Micro, Small and Medium Enterprises (MSMEs) located in Garut. The analysis technique used is multiple linear regression analysis with the help of Software SPSS 26. Multiple linear regression analysis serves to prove the research hypothesis. The results of the research analysis that both variables of innovation and creativity have a significant influence on business success with a significant level of 0.00 < 0.05. Then the R Square number of 0.643 shows that 64.3% of business success can be explained by the variables of innovation and creativity which are independent variables used in the regression equation. While the remaining 35.7% is influenced by other independent variables outside the research focus. The conclusion of this study, that the better the level of innovation and creativity that is applied in running a business, the success of the business will increase so that the business will grow and income will increase.